Photophysical properties of an alkyne-bridged bis(zinc porphyrin)-perylene bis(dicarboximide) derivative. - Odom, SA; Kelley, R; Ohira, S; Ensley, T; Huang, C; Padilha, L; Webster, S; Coropceanu, V; Barlow, S; Hagan, D; Van Stryland, E; Brédas, J; et al. (2009)
We report the synthesis, electrochemistry, and photophysical properties of a new donor-acceptor-donor molecule in which the meso carbon atoms of two zinc porphyrin (POR) units are linked through ethynylene bridges to the 1,7-positions of a central perylene-3,4:9,10-bis(dicarboximide) (PDI). In contrast to previously studied systems incorporating POR and PDI groups, this alkyne-based derivative shows evidence of through-bond electronic coupling in the ground state; the new chromophore exhibits absorption features similar to those of its constituent parts as well as lower energy features (at wavelengths up to ca. 1000 nm), presumably arising from donor-acceptor interactions. Transient absorption measurements show that excitation at several visible and near-IR wavelengths results in the formation of an excited-state species with a lifetime of 290 ps in 1% (v/v) pyridine in toluene. The absorption spectrum of this species resembles the sum of the spectra for the chemically generated radical cation and radical anion of the chromophore. The chromophore shows moderate two-photon absorption cross sections (2000-7000 GM) at photon wavelengths close to the onset of its low-energy one-photon absorption feature.